Comparison of intraoperative outcomes with single and double puncture techniques of arthrocentesis of the temporomandibular joint. Issue 8 (October 2020) - Nagori, Shakil Ahmed; Jose, Anson; Roychoudhury, Ajoy
Abstract: Evidence of differences in operator-related outcomes between single and double puncture arthrocentesis is limited. The purpose of this prospective study was to compare intraoperative outcomes with single puncture types 1 and 2, and double puncture, arthrocentesis. A total of 59 patients with 60 temporomandibular joints (TMJ) were treated sequentially by single puncture type 1 (n = 20), single puncture type 2 (n = 20), and double puncture arthrocentesis (n = 20). Total operating time, incidence of dislocation of the needle, preauricular swelling, and ease of operation were compared. Single puncture type 2 arthrocentesis took significantly less time than type 1 (p < 0.0001) or double puncture arthrocentesis (p < 0.0001), but there was no difference in operating time between single puncture type 1 and the double puncture technique (p = 0.25). There were significantly fewer dislocations of the needle with single puncture type 1 (p = 0.041) and single puncture type 2 (p = 0.033) than with double arthrocentesis. Single puncture type 2 arthrocentesis was easier than the single puncture type 1 (p = 0.001) or double puncture technique (p < 0.0001). Extravasation of fluid caused swelling in seven patients after double puncture, and in three patients each after single puncture types 1 and 2, arthrocentesis. Our results indicate that the single puncture type 2 technique is easiest and requires the least operating time. There was no difference between single puncture type 1 and double puncture arthrocentesis in terms of operating time or ease of the procedure. There were fewer operative dislocations of the needle with the single than with the double puncture technique.